2017
DOI: 10.12809/hkmj176274
|View full text |Cite
|
Sign up to set email alerts
|

Expanded newborn metabolic screening programme in Hong Kong: a three-year journey

Abstract: The Centre of Inborn Errors of Metabolism has established a comprehensive expanded newborn screening programme for selected inborn errors of metabolism. It sets a standard against which the performance of other private newborn screening tests can be compared. Our experience can also serve as a reference for policymakers when they contemplate establishing a government-funded universal expanded newborn screening programme in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A Hong Kong study reported a high incidence of CACT deficiency (3.3 per 100,000), but this involved a single confirmed case in a relatively small carrier screening population (30,448 neonates). 33 Similarly, three unrelated cases of CACT deficiency from different ethnic groups were reported in a New Zealand NBS program of 185,000 neonates screened from 2006 to 2009. 34 This unlikely cluster led to an incidence of 1.6 per 100,000 and should be viewed as an outlier against the background of most other reported incidences.…”
Section: Epidemiology Of Faods By Country and Regionmentioning
confidence: 97%
“…A Hong Kong study reported a high incidence of CACT deficiency (3.3 per 100,000), but this involved a single confirmed case in a relatively small carrier screening population (30,448 neonates). 33 Similarly, three unrelated cases of CACT deficiency from different ethnic groups were reported in a New Zealand NBS program of 185,000 neonates screened from 2006 to 2009. 34 This unlikely cluster led to an incidence of 1.6 per 100,000 and should be viewed as an outlier against the background of most other reported incidences.…”
Section: Epidemiology Of Faods By Country and Regionmentioning
confidence: 97%
“…In Taiwan two patients with hypermethioninemia (without information on the genetic basis of the alteration) were reported by Huang et al [16] as identified by an expanded newborn screening program performed on 199,922 newborns from 2001 to 2004 (1:99961), confirming the results obtained from neonatal screening for homocystinuria in that region (1 case of CBS deficiency, 1:1701591, and 16 cases of MATI/III deficiency, 1:106350; total incidence: 1:100094) [17]. A three year-journey in Hong Kong recently reported one patient with hypermethioninemia due to MAT deficiency (1:30448) [18]. In China a pilot study screened 371,942 neonates, identifying 98 cases of inborn errors of metabolism; among these three were patients affected by homocystinuria (1:123,981) [19].…”
Section: Resultsmentioning
confidence: 52%
“…1: Naylor et al [9]; 2: Zytkovichz et al [13]; 3: Frazier et al [11]; 4: CDC report [12]; 5: Torres-Sepulveda et al [14]; 6: Nagao et al [15]; 7: Wilcken et al [21]; 8: Chong et al [18]; 9: Huang et al [16]; 10: Shi et al [19]; 11: Lindner et al [20]; 12: Marcao et al [22]; 13: Couce et al [23]; 14: la Marca et al [24]; 15: Messina et al [25]; 16: Scolamiero et al [1]; 17: this paper.…”
Section: Resultsmentioning
confidence: 99%
“…An expanded newborn screening has been implemented in Hong Kong over the past few years and will become part of the routine care for all newborns delivered in public hospitals at no cost from 2021. (9,10) Currently, rDBS from the expanded newborn screening in Hong Kong are stored for 2 years after which they will be destroyed. With informed consent from parents, the laboratory could store the rDBS for longer for medical research after removing all identifying information.…”
Section: A Consent Challengementioning
confidence: 99%